La dependencia de los medios de comunicación de masas en Chile - Mattelart, Armand (Estudios Internacionales, 1970)
The models of conduct and theories transmitted by the liberal media reflect a dependent ideology, which is but one link in the imperialist strategy of the international division of labor. The holders of freedom of the press and freedom of opinion are the owners of the news media, concluding in the fact that freedom of the press is a property freedom. Two essential aspects deserve our attention: on the one hand, the material dependence or the penetration of capital, publications, broadcasts, films from abroad in the national media; and on the other, the ideological dependence or the coincidence of the messages transmitted by Chilean broadcasting sources with models imposed from outside.